DOI: 10.25148/etd.fidc004073
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Early Spatial Thinking

Abstract: I dedicate my dissertation to my family: my parents (María Rosa and Eduardo Abad), grandparents (María and José Sevilla & Chela and Ernesto Parrella), and soon-to-be husband (Pablo Casco). Everything I accomplish is guided by your love and support. v ACKNOWLEDGMENTS This dissertation could not have been completed without the support of many wonderful people. First of all, I would like to thank my advisor, Dr. Shannon Pruden, for sharing her passion for spatial research and guiding me throughout the last six ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 75 publications
(265 reference statements)
0
5
1
1
Order By: Relevance
“…This result conflicts with other current studies. Contrary to the results of this study, Abad (2018) suggested that outdoor play and outdoor experiences are the essentials for children's STS development. King et al (2019) studied twins and they revealed that environmental factors such as the outdoors affect children's STS.…”
Section: Discussioncontrasting
confidence: 99%
“…This result conflicts with other current studies. Contrary to the results of this study, Abad (2018) suggested that outdoor play and outdoor experiences are the essentials for children's STS development. King et al (2019) studied twins and they revealed that environmental factors such as the outdoors affect children's STS.…”
Section: Discussioncontrasting
confidence: 99%
“…Spatial thinking is the ability to think about the spatial world and encompasses a number of skills including mentally rotating and transforming objects and shapes, recreating patterns, and navigating around one’s environment (Sinton et al, 2013). Children and adults depend on spatial thinking for a variety of everyday situations such as remembering the location of a doll in a play room or a car in the parking lot, fitting toys in a box or suitcases in a trunk, and building block towers or Ikea furniture (Abad, 2018). Aside from being necessary for everyday tasks, spatial thinking is linked to early mathematics ability (Cheng and Mix, 2014; Verdine et al, 2017) and predicts future entry in Science, Technology, Engineering, Mathematics (STEM) fields (Humphreys et al, 1993; Shea et al, 2001; Wai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For this task, we categorized toys rated with 4's or 5's as “highly spatial” (e.g., set of magnetic tiles) and pitted them against “less‐spatial” educational toys that had been rated between 1 and 3 (e.g., musical instrument). Toys included in this task had also been rated by 298 undergraduate students (Abad, 2018) as gender‐neutral, and appropriate for play by either boys or girls; in this pilot study, no sex differences in children's engagement with toys used for this task were found. We matched these pairings based on price and were careful to select gender‐neutral toys because two factors appear to bias a parent's decision when choosing a toy to hypothetically purchase: (1) economic and other cost considerations; and (2) gender typicality of toys.…”
Section: Methodsmentioning
confidence: 95%
“…There were 12 trials in which the mother was asked to decide between two educational toys: (1) a “highly spatial” educational toy; and (2) a “less‐spatial” educational toy (see Figure 1). Instructions read, “Which of the two toys on your screen would you prefer to buy for your child?” The toys included in the task had previously been rated on a 1 (“least spatial”) to 5 (“highly spatial”) scale by spatial development experts in the field (Abad, 2018). For this task, we categorized toys rated with 4's or 5's as “highly spatial” (e.g., set of magnetic tiles) and pitted them against “less‐spatial” educational toys that had been rated between 1 and 3 (e.g., musical instrument).…”
Section: Methodsmentioning
confidence: 99%